Significant thrombocytopenia associated with the addition of rituximab to a combination of fludarabine and cyclophosphamide in the treatment of relapsed follicular lymphoma - Leo, Eugen; Scheuer, Lars; Schmidt-Wolf, Ingo G. H.; Kerowgan, Mohammed; Schmitt, Christina; Leo, Albrecht; Baumbach, Tanja; Krämer, Alwin; Mey, Ulrich; Benner, Axel; Parwaresch, Reza; Ho, Anthony Dick (European journal of haematology, 2004)
Fludarabine in combination with cyclophosphamide is an effective treatment for newly diagnosed as well as relapsed follicular lymphoma. The anti-CD20 antibody rituximab has been employed successfully for the same indications. No such data were available on a combined use of these agents. Therefore, we conducted a phase II study to evaluate the safety and efficacy of a combination of rituximab (375 mg/m2), fludarabine (4 x 25 mg/m2) and cyclophosphamide (1 x 750 mg/m2), for the treatment of relapsed follicular lymphoma. An unexpected, severe hematologic toxicity with significant, prolonged thrombocytopenias WHO grade III/IV in 6 (35%) of 17 patients treated in total occurred, leading to early termination of the trial. Cytologic and serologic analyses point toward a direct toxic effect. Older patients (mean age 64.7 vs. 56.5 yr) were significantly (P = 0.02) more likely to suffer from this toxicity, whereas no other clinical or hematologic parameter differed statistically between the patients suffering from thrombocytopenia and those who did not. The addition of rituximab to fludarabine/cyclophosphamide employed at doses given above in relapsed follicular lymphoma may have led to this increase in thrombocytopenias. Therefore, caution should be exercised when combining these drugs for the treatment of patients with relapsed follicular lymphoma, especially when treating older patients.
Gesehen am 30.06.2021